Clifford, the small red puppy - Bridwell, Norman (New York : Scholastic, 1985)
Clifford begins life as a very small red puppy, but once he starts growing into a very large red dog there seems no limit to his potential size.
Reference and Research Book News.
1.9
K-3
330L
J
Keywords: Dogs -- Fiction; Size -- Fiction; Dogs -- Fiction; Clifford (Fictional character : Bridwell) -- Fiction